The Effect of Ultrafiltration Rate Level in Blood Pressure Status Changes in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Elpiani Br Depari; Mona Herni Cristina Ritonga; Dewi Cahaya Br Hutabarat; Indria Sisilia Agata; Yoga Wijaya (Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Intradialytic blood pressure changes are common complications in patients undergoing hemodialysis and are suspected to be influenced by the ultrafiltration rate (UFR). These blood pressure fluctuations may affect patient morbidity and mortality through cardiovascular events. Objective: This study aimed to analyze the effect of ultrafiltration rate levels on intradialytic blood pressure status changes based on systolic blood pressure and mean arterial pressure (MAP) parameters. Methods: This study was a prospective observational analytic study conducted among patients with chronic kidney disease (CKD) undergoing hemodialysis at Grandmed Hospital Lubuk Pakam. The UFR was categorized into <10, 10–13, and >13 mL/kg/hour. Blood pressure status changes were classified as stable, hypotensive, and hypertensive. Data were analyzed using the chi-square test with a significance level of p<0.05. Results: A significant association was found between UFR levels and blood pressure status changes based on systolic blood pressure (χ²=12.691; p=0.013), but not on MAP (χ²=7.233; p=0.124). The highest proportion of blood pressure changes was observed in the >13 mL/kg/hour UFR group. Conclusion: Ultrafiltration rate levels significantly influence intradialytic systolic blood pressure changes, higher UFR associated with increased hemodynamic instability.